Perancangan Sistem Informasi Persediaan, Penjualan & Pembelian Barang pada PT.XYZ Berbasis Web - Ellyse Obe Johanis; Hery Hery; Eric Jobiliong; Calandra A. Haryani; Andree E. Widjaja (Yayasan Literasi Sains Indonesia, 2025)
In today's digital era, internet technology plays a vital role in the business sector, enabling companies to grow more rapidly and adapt to market demands. The integration of information technology has transformed business operations, as evidenced by the increasing number of large enterprises adopting such technologies. One of the main advantages is the ability to conduct online transactions, allowing customer to make purchases without queuing and enabling employees to work more efficiently. Consequently, transaction processes become faster and more convenient, while also expanding the company’s customer base and increasing profitability. This study presents the development of an information system using the prototyping methodology. The proposed system is built using PHP programming language and the CodeIgniter framework. The system design includes use case diagrams, activity diagrams, class diagrams, and entity relationship diagrams. The implemented information system aims to optimize the purchasing and sales processes at PT. XYZ, enhancing overall business efficiency and supporting strategic decision-making. The final outcome of this research is a web-based application that facilitates and streamlines product sales and purchases within the company.